CONTEMPORARY BIOMARKERS OF BLOOD-BRAIN BARRIER INJURY AND NEUROINFLAMMATION IN PRETERM INFANTS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY - Hadzimuratovic, Emina; Brankovic, Suada; Hadzimuratovic, Admir (Sanamed, 2026)
Background: Hypoxic–ischemic encephalopathy (HIE) is a major cause of neonatal morbidity and long-term neurodevelopmental impairment, particularly in preterm infants. Early diagnosis remains challenging, and there is growing interest in biomarkers that reflect underlying mechanisms such as neuroinflammation and blood–brain barrier disruption. Objective: To evaluate the diagnostic and prognostic value of selected circulating biomarkers in preterm infants with HIE, with emphasis on a multimarker approach. Methods: This prospective cohort study included 120 preterm infants (gestational age 28–36 weeks), divided into HIE (n=90) and control (n=30) groups. Serum levels of NR2 antibodies, endothelin-1, glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL) were measured at 24–48 hours, day 5–7, and day 14. Statistical analysis included t-test, ANOVA, correlation analysis, logistic regression, and ROC curve analysis. Results: Biomarker levels were significantly higher in the HIE group (p<0.001). GFAP and NfL showed the highest diagnostic performance (AUC 0.86 and 0.88). The combined model achieved the best accuracy (AUC=0.89). Biomarker levels correlated with disease severity. Conclusion: A multimarker approach improves diagnostic accuracy and may support early risk stratification and individualized management in preterm infants with HIE.